Risk factors and intervention strategies for post-traumatic stress disorder following spinal cord injury: a retrospective multivariate analysis of 195 cases - Jie Jiang; Qi Sun; Jingjun Xie; Jianwei Sun (BMC Psychology)
Abstract Objective To examine the risk factors and intervention strategies for post-traumatic stress disorder (PTSD) in patients with spinal cord injuries (SCI). Methods A retrospective study involving 195 SCI patients (from January 2023 to December 2024) divided them into two groups: those with PTSD (n = 61) and those without PTSD (n = 134). Various demographic, clinical, and complication factors were analyzed, with significant differences further explored using multivariate logistic regression. Results Among 195 SCI patients, 61 (31.28%) developed PTSD. Significant differences were observed between the PTSD and non-PTSD groups in terms of age, sex, education level, severity of SCI, predicted rehabilitation outcome, and number of complications (P < 0.05). No significant differences were found in marital status, personal income level, cause of injury, pulmonary and urinary tract infections, pressure ulcers, deep vein thrombosis, autonomic nervous system dysfunction, or psychological disorders (P > 0.05). Multivariate logistic regression analysis identified age ≥ 45 years (95% CI: 2.884–19.513, OR = 7.502, P < 0.001), female sex (95% CI: 1.225–6.736, OR = 2.873, P = 0.015), education level < 12 years (95% CI: 1.160–6.409, OR = 2.726, P = 0.021), SCI severity grade C or higher (95% CI: 1.051–5.965, OR = 2.503, P = 0.038), non-self-sufficient predicted rehabilitation outcome (95% CI: 1.148–10.799, OR = 3.522, P = 0.028), and more than two complications (95% CI: 4.818–31.544, OR = 12.328, P < 0.001) as independent risk factors for PTSD. Conclusion Prompt recognition and specific interventions for high-risk spinal cord injury patients are crucial for minimizing PTSD and enhancing results.